The Effect of Sleep Deprivation and Retroactive Interference on Offline Learning in Tennis Simulated Game - Ahmad Nikravan; Valiollah Kashani; Elahe Mostafaifar (University of Tehran, 2017)
This study aimed at investigating the effect of sleep deprivation and retroactive interference on offline learning in tennis simulated game. Based on the questionnaires related to the variables under study, 50 female students of Semnan University (age range 19-25 years) were selected as the sample and divided into 5 groups: perfect sleep, sleep deprivation, perfect sleep and retroactive interference, sleep deprivation and retroactive intervention and training with rest interval less than 1 hour. A tennis simulated game (with rules and scoring similar to a real game) was performed to measure offline learning. One-way ANOVA and ANOVA with repeated measures were used for inferential statistics at a significance level (P≤0.05). The results showed that the differences in offline learning (Sig=0.001) and retention scores (Sig=0.001) were significant among the research groups. In those groups with sufficient rest intervals between each two sessions and full rest, the level of their performance was higher in the next day than the previous day. Opposite effects were observed with sleep deprivation and retroactive interference. Therefore, those who are learning a skill should pay attention to their daily activities and sleep patterns to prevent a disruption to skill learning and to take advantage of their practices.